Beneficiation of feldspar - Juan, Manuel Luis D. (College of Engineering, 1969)
Capacity: 300,000 lbs crude ore/day -- Fixed capital investment: 4,842,361 -- Operating cost at maximum production: 1,116,170 -- Maximum annual production: 16,149 tons/year -- Sales at maximum production: 1,534,830 -- Percent return on investment before taxes: 8.85% -- Percent return on investment taxes taxes: 8.21% -- Pay-out time: 11.3 years -- Break-even point: 38% of plant capacity -- Shutdown point: 12% of plant capacity